SELECTING THE BEST SMARTPHONE USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (Case Study Lenovo, Asus and Oppo) - Supit, Christoffel C.T; Pangemanan, Sifrid S.; Tumewu, Ferdinand . (Universitas Sam Ratulangi, 2018)
Abstract: In Manado city almost of all the top smartphone brands can be met in this city because the high excitability of peoples in Manado that encourage them to buy smartphone and fulfil their curious of the several smartphone even the brand that not enter the Indonesian marketplace or in other words unfamiliar smartphones like several brands such as Lenovo, Asus and Oppo. Based on the research problem, the objectives of this research is to identify which smartphone people prefer the most. This research used quantitative method. Quantitative research seeks to quantify the data. The method used to this research is Analytical Hierarchy Process (AHP). AHP is a method for ranking data and selecting the best given criteria. The result of this research has showing Price, Durability and Hardware Specification are the most important criterias. Based on the result would be well advised to pay attention on Price, Durability and Hardware SpecificationÂ before buying a Smartphone.Keywords: consumer needs, customer expectation, analytical hierarchy process.